Preferential and asymmetric interaction of linker histones with 5S DNA in the nucleosome. - Hayes, J J (1993)
We establish that linker histones H1 and H5 bind preferentially to a Xenopus borealis somatic 5S RNA gene associated with an octamer of core histones rather than to naked 5S DNA. This preferential binding requires free linker DNA to either side of the nucleosome core. Incorporation of a single linker histone molecule into the nucleosome protects an additional 20 bp of linker DNA from micrococcal nuclease digestion. This additional DNA is asymmetrically distributed with respect to the nucleosome core. Incorporation of linker histones causes no change to the cleavage of DNA in the nucleosome by hydroxyl radical or DNase I.